Relationships between geomagnetic Ар-indeх and parameters of the immunity in patients with multiple sclerosis and radiculopathies - Popovych, Igor; Gozhenko, Anatoliy; Badiuk, Nataliya; Napierała, Marek; Muszkieta, Radosław; Zukow, Walery; Yanchij, Roman; Lapovets’, Natalia; Lapovets’, Lyubov; Tserkovnyuk, Ruslan; et al. (Journal of Education, Health and Sport, 2021)
Background. The effect of geomagnetism on human immunity has so far been studied through long-term observations. We set ourselves the goal of detecting the immediate immunotropic effects of the Earth’s magnetic field by analyzing the relationships between immunity parameters and the geomagnetic Ap-index. Material and methods. The object of observation were 74 patients with multiple sclerosis and 14 patients with radiculopathies, who in the period from September 2014 to November 2018 conducted a one-time assessment of immune status by the relative content in the blood of lymphocytes of CD3+, CD4+, CD8+, CD25+, CD56+ and CD19+ phenotypes and serum level of Immunoglobulines M, G, A as well as CIC and IL-1β. On the day of blood capture and during the previous 7 days, retrospectively recorded the geomagnetic Ap-index, using a publicly available information resource http://wdc.kugi.kyoto-u.ac.jp/kp/index.html. Results. During the week, the average level of Ap-index ranged from 12÷20 nT. The correlation coefficients between the Ap-index on the day of blood collection and 1, 3 and 7 days before it and the level of CD3+CD4+ lymphocytes were -0,57; -0,48; -0,55 і -0,52 respectively, while on other days were in the range of -0,35÷0,05. In contrast, with the level of CD56+ lymphocytes Ap-index correlates positively and almost mirror (0,56; 0,43; 0,54 і 0,57 respectively and 0,34÷-0,08), due to the reciprocity of their levels (r=-0,80). Also positive, but much weaker, correlates the Ap-index with the level of CD25+ lymphocytes (0,35; 0,25; 0,45 і 0,31 respectively and 0,22÷-0,14). In contrast, with the level of IL-1β Ap-index correlates significantly only on the day of blood collection and 2 days before (r=0,21 and 0,31 respectively), and with other registered parameters of immunity the correlation is insignificant. The canonical correlation between Ap-indices for 7 days before and on the day of blood collection, on the one hand, and the levels of CD4+, CD56+, CD25+ and CD8+ lymphocytes and the concentration of IgM and IL-1β - on the other hand, was very strong: R=0,741; R2=0,549; χ2(42)=130; p<10-6. Conclusion. <span style="font-family: ’Times New Roman’; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Disturbances of the geomagnetic field (Ap-index) has a significant immediate modulating effect on the level of immune parameters in the blood, mostly T-helpers (suppressor) and natural killers (enhancing).